136PHelicobacter pylori-positive gastric diffuse large B-cell lymphoma: A subset with distinct prognostic features. (24th November 2019) - Cheng, Y; Ma, X; Yang, J
Abstract: Background: Recent studies indicated that Helicobacter pylori (H. pylori) exerts an oncogenic effect on the development of gastric diffuse large B-cell lymphoma (DLBCL). However, the effect of H. pylori status on prognosis of gastric DLBCL remains unconfirmed. Methods: In the present study, H. pylori status was assessed by histologic examinations, supplemented by results from urease breath test and/or serological analyses where available. Staging tumours included a detailed medical history, physical examination which included peripheral lymph nodes and Waldeyer's ring, complete hematological biochemical examinations containing serum lactate dehydrogenase (LDH), computed tomography (CT), gastric endoscopy, endoscopic ultrasonography, positron emission tomography (PET)/CT, and bone marrow aspiration and biopsy. Survival curves were estimated by Kaplan-Meier univariate analyses. The prognostic value of H. pylori was verified by both univariate and multivariate analyses. Results: One hundred and twenty-nine patients diagnosed with primary de novo gastric DLBCL in West China Hospital of Sichuan University were included from 1st January 2009 to 31st May 2016. Over a median follow-up of 45.0 months (range 2-107), mean event-free survival (EFS) was 83.1 months (95% CI 72.7-93.5) and mean overall survival (OS) was 89.9 months (95% CI 80.9-98.9) in patients infected with H. pylori, compared with 62.0 months (95% CI 50.7–73.3) and 72.2 months (95% CI 61.6–82.9), respectively, in H. pylori-negative subgroup (P = 0.010 and P = 0.020 for differences in EFS and OS between groups, respectively). Patients with H. pylori infection had significantly better 5-year EFS and OS than H. pylori-negative subgroup (5-year EFS, 71% vs 47%, P = 0.010; 5-year OS, 79% vs 58%, P = 0.020). Older age, advanced Lugano stage, higher IPI score, and negative H. pylori status were independent negative prognostic indicators of survival outcomes. Conclusions: H. pylori status in de novo gastric DLBCL can be a promising predictor of disease outcomes, and patients with negative H. pylori status should be followed up carefully since they tend to have a poor outlook. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.